Anticipatory Regulation: Lessons from fracking and insights for Greenhouse Gas Removal innovation and governance. (August 2022) - Aczel, Miriam; Heap, Richard; Workman, Mark; Hall, Stephen; Armstrong, Harry; Makuch, Karen
Abstract: The UK has incorporated a net-zero emissions target into national legislation. A range of Greenhouse Gas Removal (GGR) options will likely play a key role in the government's strategy toward meeting this goal. Governance frameworks will need to be developed to support GGR development and manage the potential impacts, particularly those on the diverse local communities where the various options will be deployed. This research examines the UK's experience with development and regulation of shale gas - using the technologies of hydraulic fracturing combined with horizontal drilling - with a focus on governance and the implications for the development and widespread deployment of GGR. We evaluate the approach used against the principles of good governance, which emphasizes the critical role that local communities and publics play in deployment. The UK's top-down governance of shale gas highlights the risk of regulation driven by assumptions about national and local need, value and a lack of transparency or meaningful stakeholder participation in decision-making. The use of existing legislative frameworks for conventional fossil fuel extraction proved inadequate to address unanticipated consequences such as induced seismicity. Moreover, the support for unconventional hydrocarbons in UK energy policy appeared inconsistent with the goal of meeting greenhouse gas targets and passing significant legislation in 2019 to bring carbon emissions to net-zero. To gain social acceptance at the local level, deployment of new technologies needs to be evaluated from a variety of framings and viewpoints. Where new technologies or practices are deployed, such as fracking and GGR, the knowledge and understanding of the impacts - a fundamental principle of good governance - may be less certain or more contested. Early inclusion and participation of local communities would allow issues of concern to inform how trials are undertaken and regulation designed. This anticipatory and participatory approach fits with the principles of good governance and procedural justice, which can help build the trust needed to ensure social legitimacy leading to development and implementation of technological innovations. Highlights: Deployment of greenhouse gas removal technologies has potential for significant impacts on local communities Governance frameworks that incorporate diverse public perspectives are needed to ensure social acceptance of GGR The UK's experience with 'fracking' provides valuable lessons for the development of GGR frameworks Anticipatory Regulation that aims to build trust, social legitimacy, and institutional capacity can further implementation of GGR technologies